2017
DOI: 10.21873/anticanres.11597
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Cancer Stem Cell Markers ALDH1A1 and CD133 in Lung Adenocarcinoma

Abstract: Abstract. Background/Aim: Aldehyde dehydrogenase-1A1 (ALDH1A1) and CD133 have been identified as markers of cancer stem cells (CSCsDespite continuous efforts to improve therapeutic response, lung cancer is the most common cause of cancer-related deaths in Japan, with adenocarcinoma by far the most common histology, accounting for nearly 70% of lung cancer cases (1). Cancer stem cells (CSCs) have the ability for selfrenewal and multipotently differentiate (2). CSCs may be highly resistant to chemotherapy and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…CD133 expression was higher only in PCS2-bead-bound H1693 cells and undetectable in all three remaining cell lines. It is known that the expression of two lung CSC biomarkers ALDH and CD133 do not correlate 21,24,25 , and we did not detect CD133 expression in either the PCS2 bound or the unbound fractions of H358, H460, and H1975 NSCLCs (Fig. 2B–E).…”
Section: Resultsmentioning
confidence: 59%
“…CD133 expression was higher only in PCS2-bead-bound H1693 cells and undetectable in all three remaining cell lines. It is known that the expression of two lung CSC biomarkers ALDH and CD133 do not correlate 21,24,25 , and we did not detect CD133 expression in either the PCS2 bound or the unbound fractions of H358, H460, and H1975 NSCLCs (Fig. 2B–E).…”
Section: Resultsmentioning
confidence: 59%
“…Previous studies reported that CSC biomarkers such as NANOG [ 21 , 22 ], OCT4 [ 21 , 23 ], SOX2 [ 21 , 24 ], KLF4 [ 21 , 25 ] and ALDH1A1 [ 21 , 26 ] were associated with a poor prognosis in several cancers. The correlation analysis indicated that the average expression of the five cancer stemness biomarkers was tightly associated with TBX21 in the integrated GEO dataset ( r ≥ 0.850, P < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CSC-targeted therapy and treatment strategies are urgently needed. CSCs can be recognized by their specific markers, such as ALDH1A1 and CD133, (Miyata et al, 2017) and by their cellular traits, such as colony formation and other aggressive behaviors (Yongsanguanchai et al, 2015;Tiran et al, 2017).…”
Section: Downloaded Frommentioning
confidence: 99%